Paraquat Pesticide Exposure to the Incidence of Anemia in Sugarcane Plantation Workers “X” - Vivi Oktari; Muhammad Irsan Saleh; Mohammad Zulkarnain; Suheryanto Suheryanto (Indonesian Journal of Global Health Research, 2025)
Pesticide poisoning, especially paraquat, is a significant health problem for agricultural workers, including sugarcane plantation workers in Indonesia. This study aims to evaluate the relationship between pesticide use and hemoglobin levels. This study is a descriptive study to find the correlation between paraquat pesticide exposure and hemoglobin levels. Quota sampling technique was used to collect 51 samples. Data were collected through interviews, observation of the use of Personal Protective Equipment (PPE), and measurement of hemoglobin levels by laboratory methods on 51 workers exposed to paraquat pesticide. The Chi-Square test was used to analyze the relationship between the use of PPE and the level of pesticide poisoning as measured by hemoglobin levels. The results showed that incomplete use of PPE was associated with a decrease in workers' hemoglobin levels. As many as 40% of workers who did not use PPE experienced a significant decrease in hemoglobin levels compared to workers who used complete PPE. The calculated Chi-Square value is 6.45 with a p value = 0.011 (p < 0.05) which indicates a significant relationship between the use of PPE and hemoglobin levels in sugarcane plantation workers. Based on these results, it can be concluded that proper use of PPE can reduce the risk of pesticide poisoning and maintain hemoglobin levels at normal levels.